Caracterización sociodemográfica de la salud materna en el Vichada , 2011-2015: una mirada desde la morbimortalidad (2019)
In order to identify some of the social and demographic factors related to maternal health, morbidity and mortality in Vichada in the years 2011 to 2015, two studies were designed, one ecological analytical and one of cases and controls. In the period 2011 to 2015, the trend of maternal mortality in life was the reason for maternal mortality from 228.57 to 764.82 deaths per 100,000 live births. 80% (n: 20) of maternal mortalities corresponded to early deaths and 40% (n: 10) of mortalities were attributed to obstetric hemorrhage. The morbidity ratio mostly increased in the period 2012-2015, from 13.18 to 37.28 cases per 1,000 live births, vascular failure was more frequent with 22.26% of the total cases. The risk of dying from a manager without controls compared to having more than five times (Rate of rates: 4.63, 95% CI 1.22-25.85, P 0.02) and that of pregnant women suffering from a serious complication that (Rate of fees : 5.51, 95% CI 3.15-9.63, P <0.01).